EFFECT OF ZINC OXIDE NANOPARTICLES ON THE THERMAL, MECHANICAL AND WATER ABSORPTION PROPERTIES OF POLYLACTIC ACID/CHITOSAN COMPOSITES - Rihayat, Teuku; Nurhanifa; Cionita, Tezara (International Journal of Research -GRANTHAALAYAH, 2020)
The aim of this work is to improve the mechanical, thermal and water absorption properties of PLCHZ composites. The formation of the composites are mixing polylactic acid with zinc oxide nanoparticles (ZnO) and chitosan as filler. It produced through the precipitation method using a water bath under a temperature of 60 oC. Five prepared samples are pure PLA, PLCH, PLCHZa, PLCHZb and PLCHZc. The incorporating eﬀect of fillers on the properties of samples is investigated in terms of mechanical, thermal and water absorbtion test. The result showed that mechanical and thermal properties increased with the addition of ZnO nanoparticles compared to pure PLA and PLCH. Nevertheless, those properties increased up to 2 wt% of ZnO nanoparticles loading but decreased when it content is increased up to 3 wt% and 4 wt%. PLCHZa with the smallest content of 2 wt% ZnO nanoparticles showed the highest value of 15 MPa in tensile strength and 330.6 oC in thermal resistant. In water absorbtion test, PLCHZc with 4 wt% ZnO has better absorb ability as well as the lowest percentage absorption rate of 0.02% to 0.03%. It can be conclude that ZnO nanoparticles play an important role in the main properties of polymer composites.